Artistic significance and psycholinguistic analysis of the story "Yulduzlar mangu yonadi" (Zien Journal of Social Sciences and Humanities, 2022)
This article reveals the semantics of speech in Uncle Murad's story "Yulduzlar mangu yonadi" through artistic means and provides a psycholinguistic analysis of the hero's psyche.